Block kidney transplantation from pediatric donors - Méndez Chacón, Pedro (2005)
Abstract Objective: To determine both kidneys from pediatric donors acceptance in block kidney transplantation. Material and Methods: Age of the six donors ranged form 14 months to 10 year-old. The death cause was cranial trauma. Receptors’ ages ranged between 15 and 48 years with weight less than 50 kg. Both kidneys were removed in block. The transplants surgical technique consisted of both terminal-lateral anastomosis of the donor’s aortic segment and inferior cava vein anastomosis to receptor’s iliac vessels; both ureters were separately anastomosed to the bladder. The allograph was located in one iliac fossa. Results: The block allograph worked immediately. Four of six receptors kept adequate renal function in an average of four years surveillance time. One of the block’s allograph was lost because of severe vascular rejection and another because of indiscipline in the use of immunosuppressive medication. Kidney’s ultrasonographic series revealed size increase up to 55% by the third month of transplantation. Conclusion: We suggest that kidneys from donors less than 3 year-old should be used as block transplant and kidneys coming from older donors should be used as simple kidney transplants. Our novel experience suggests that it is possible to successfully transplant kidneys in block from very little children to older receptors.